Can combining vaginal and rectal progesterone achieve the optimum progesterone range required for implantation in the HRT-FET model?. Issue 6 (June 2020) - Alsbjerg, B.; Thomsen, L.; Elbaek, H.O.; Laursen, R.; Povlsen, B.B.; Haahr, T.; Humaidan, P.
Abstract: Research question: What is the ongoing pregnancy rate (OPR) in frozen embryo transfer (FET) cycles, using combined rectal and vaginal progesterone in hormonal replacement therapy (HRT)? Design: A prospective cohort study ( n  = 277) including 239 HRT-FET cycles with serum progesterone measurements studying combined vaginal (90 mg/12 h) and rectal (90 mg/12 h) progesterone administration and single blastocyst transfer on the sixth day of progesterone administration. A total of 134 responses to questionnaires covering convenience and side-effects were collected. Results: The median serum progesterone level was 45 nmol/l (range 2–150 nmol/l). Overall positive HCG rate, OPR at week 12 and pregnancy loss rates were 62%, 44% and 29%, respectively. A non-linear relationship between serum progesterone levels and OPR was found. Crude odds ratio for OPR in the high progesterone group (>45 nmol/l) was 0.56 (95% CI 0.32 to 0.98; P  = 0.04) compared with the intermediate progesterone group (28–45 nmol/l). Discomfort after rectal progesterone administration was reported on the embryo transfer day and on the day of pregnancy scan 5 weeks later by a total of 18% (16/87) and 17% (8/47) of patients, respectively. Discomfort related to vaginal administration increased significantly over time and was reported by 18% (16/87) on the day of embryo transfer compared with 45% (21/47) on the day of pregnancy scan ( P < 0.002). Conclusions: Combined rectal and vaginal progesterone in HRT-FET cycles resulted in higher median progesterone levels compared with vaginal administration alone. This study suggests that an upper threshold for serum progesterone exists and that above this concentration serum progesterone levels decrease the OPR. Rectally administered progesterone was well tolerated by patients.